2011
DOI: 10.1080/00927872.2011.616429
|View full text |Cite
|
Sign up to set email alerts
|

Finite Dimensional Hopf Algebras Over the Dual Group Algebra of the Symmetric Group in Three Letters

Abstract: We classify finite-dimensional Hopf algebras whose coradical is isomorphic to the algebra of functions on 3 . We describe a new infinite family of Hopf algebras of dimension 72.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 10 publications
0
38
0
Order By: Relevance
“…This classification was completed by Angiono and Garcia Iglesias in [AG19], where it is also shown that all Hopf algebras whose coradical is an abelian group algebra are cocycle deformations of their associated graded Hopf algebras. For more classification results of non-semisimple Hopf algebras in which cocycle deformations appear, see [AAIMV14], [FGM19], [GarM15], [GruM] and [AV11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This classification was completed by Angiono and Garcia Iglesias in [AG19], where it is also shown that all Hopf algebras whose coradical is an abelian group algebra are cocycle deformations of their associated graded Hopf algebras. For more classification results of non-semisimple Hopf algebras in which cocycle deformations appear, see [AAIMV14], [FGM19], [GarM15], [GruM] and [AV11].…”
Section: Introductionmentioning
confidence: 99%
“…The first case appears in [IM11]. For the second case, the resulting double-twisted Hopf algebras α H α −1 appear in [AV11].…”
Section: Introductionmentioning
confidence: 99%
“…We recall that a Hopf algebra A is said to be pointed if A (0) = kG(A) and copointed when A (0) = k G for some non-abelian group G. Our main result is the following. Finite-dimensional copointed Hopf algebras over k S 3 are classified in [AV1].…”
Section: (C ⊗ Id)(id ⊗C)(c ⊗ Id) = (Id ⊗C)(c ⊗ Id)(id ⊗C)mentioning
confidence: 99%
“…Nonpointed Hopf algebras with Chevalley property known to exist [AV1,AV2]. 9 dim p 3 q, p 2 q 2 , p 2 qr: For dimensions 88, 100, 84, 90, the classification of the pointed Hopf algebras was completed for those with coradical a group algebra of order a power of 2 in [Ni] and [Gr1].…”
Section: Open Casesmentioning
confidence: 99%